A Compact Quint-Band Bandpass Filter Based on Stub-Loaded Resonators - Farhat, M.; Munisami, J.; Abdul-Niby, M.; Nahas, M. (Engineering, Technology & Applied Science Research, 2017)
This paper presents a planar quant-band bandpass filter with a high out-of-band rejection. The filter is based on inter-coupled stub-loaded resonators, where pairs of resonators are electromagnetically coupled to each other and the feed lines. This results in excitation of passbands, where the first and the third passbands are generated by λ/4 stub-loaded resonators. The second and the fifth passbands are excited by λ/2 stub-loaded resonators. And the fourth passband is generated by λ/2 resonators. The proposed technique provides sufficient degree of freedom to control the center frequency and bandwidth of the five passbands. In addition, the seven transmission zeros created around the passbands results in a quant-band filter with high selectivity, sharp 3dB cut-off frequency, high isolation, and low passband insertion-loss. Design methodology and simulation results of the filter are provided.